2012
DOI: 10.1097/brs.0b013e31826ba7cd
|View full text |Cite
|
Sign up to set email alerts
|

The Pressure Distribution of Cerebrospinal Fluid Responds to Residual Compression and Decompression in an Animal Model of Acute Spinal Cord Injury

Abstract: Although extradural compression exists at the site of injury, lumbar CSFP may not accurately indicate CSFP cranial to the injury. Decompression may provide immediate, though perhaps partial, resolution of the pressure differential. CSFPPA was not a consistent indicator of decompression in this animal model. These findings may have implications for the design of future clinical protocols in which CSFP is monitored after acute SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…Jones et al described two separate studies in 2012 utilizing a porcine model of weight drop and compression SCI followed by decompression surgery 4 h after primary injury (Jones et al, 2012a, 2012b). In one study, the authors investigated the morphological alterations to the dura and spinal cord following persistent compression and surgical decompression in Yucatan pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al described two separate studies in 2012 utilizing a porcine model of weight drop and compression SCI followed by decompression surgery 4 h after primary injury (Jones et al, 2012a, 2012b). In one study, the authors investigated the morphological alterations to the dura and spinal cord following persistent compression and surgical decompression in Yucatan pigs.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, it was shown in human [10] and in experimental settings [47] that a differential in CSF pressure across the injury site may occur. This emphasises the need for measuring CSF pressure caudal and rostral to the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent this anatomical limitation, other experimental studies have used bigger animals such as cats [45] or Yucatan miniature pigs [46,47]. Compared to rats, bigger animals like pigs offer the major advantage to have a ratio between volumes of spinal cord and subarachnoidian space very similar to humans.…”
Section: Discussionmentioning
confidence: 99%
“…In an SCI animal model, Jones et al 16 found that an enlarged cord immediately occluded the subarachnoid space in severe SCI, and CSF pressure was only partially decreased by epidural decompressive surgery. 11 Okada et al 17 found that systemically increased intraspinal pressure is involved in the pathogenesis of ascending myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional epidural decompression seems adequate during surgery, postoperative MRI often reveals that the swollen cord has filled the subarachnoid space. 9,10 Obvious cerebrospinal fluid pressure (CSFP) elevation has been shown after SCI in preclinical and clinical studies, [11][12][13] and CSFP elevation may lead to neurological dysfunction. 14 Meagher et al 15 and Planner et al 2 reported that disruption of CSF dynamics was the major cause of SPAM.…”
Section: Discussionmentioning
confidence: 99%